2003
DOI: 10.3233/jad-2003-5407
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids and risk of cognitive impairment and dementia

Abstract: It has been suggested that the dietary intake of omega-3 polyunsaturated fatty acids could be inversely related to the risk of dementia and cognitive decline. This analysis examined the association between plasma concentration of omega-3 polyunsaturated fatty acids and prevalence and incidence of cognitive impairment and dementia. Data are reported on subjects 65 years or older who had a complete clinical evaluation at the first two waves (1991-1992 and 1996-1997) of the Canadian Study of Health and Aging. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 34 publications
5
69
1
Order By: Relevance
“…6 One possible reason for these inconsistent results is the limited ability of dietary recall surveys and food frequency questionnaires to quantify blood levels of fatty acids. 7,8 In the Framingham original cohort, participants in the top quartile of plasma phosphatidylcholine docosahexaenoic acid (DHA) levels had 37% and 47% lower risks of Alzheimer disease (AD) and all-cause dementia, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 One possible reason for these inconsistent results is the limited ability of dietary recall surveys and food frequency questionnaires to quantify blood levels of fatty acids. 7,8 In the Framingham original cohort, participants in the top quartile of plasma phosphatidylcholine docosahexaenoic acid (DHA) levels had 37% and 47% lower risks of Alzheimer disease (AD) and all-cause dementia, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…3 While several large epidemiologic studies 4,5 have shown an association between the estimated intake of fatty fish and a lower risk for dementia, some other investigations have failed to confirm such a protective association. 6 One possible reason for these inconsistent results is the limited ability of dietary recall surveys and food frequency questionnaires to quantify blood levels of fatty acids. 7,8 In the Framingham original cohort, participants in the top quartile of plasma phosphatidylcholine docosahexaenoic acid (DHA) levels had 37% and 47% lower risks of Alzheimer disease (AD) and all-cause dementia, respectively.…”
mentioning
confidence: 99%
“…Results for other nutrients studied (antioxidants, dietary patterns, multivitamins) are not presented here. Of the 33 included papers, 19 were cohort studies including 11 on folate, other B-group vitamins and/or homocysteine [26][27][28][29][30][31][32][33][34][35][36] and eight on fish, DHA or EPA [37][38][39][40][41][42][43][44]. The remaining 14 were randomized controlled trials (RCTs) including ten on folic acid with or without other B-group vitamins [45][46][47][48][49][50][51][52][53][54], and four on mixed fatty acids [55][56][57][58].…”
Section: Overall Search Findingsmentioning
confidence: 99%
“…A consensus conference assigned 2 diagnoses for each person examined, one according to the criteria used in CSHA-1 and the other according to the more recent DSM-IV criteria for AD (8) and National Institute of Neurological Disorders and Stroke-Association internationale pour la recherche et l'enseignement en neurosciences (NINDS-AIREN) criteria for vascular dementia (9). Blood samples were collected from some of those who were clinically examined, and apolipoprotein E (apoE) status and levels of omega-3 fatty acids were determined (10,11). Where participants had died before or during the follow-up study, the date and cause of death were obtained from the relevant provincial registrar of vital statistics; as well, a relative or other informant was interviewed to assess the subject's physical and cognitive status 3 months prior to death.…”
Section: First Follow-up (Csha-2)mentioning
confidence: 99%